The Extent of Conformity of Academic Programs Outcomes at the College of Engineering, The University of Jordan to ABET Standards from the Viewpoint of Faculty Members and Quality Assurance Representatives - د. دلال مصطفى عبدالله هواش (University of Science and Technology, Yemen, 2020)
The current study aimed to identify the extent to which the academic outcomes of the programs of the Faculty of Engineering at the University of Jordan conform to the American accreditation standards "ABET". To achieve the study objective, the qualitative method was followed and three tools were used: standardized open-ended interviews, participant observation, and analysis of documents collected from the field. Major findings revealed that engineering departments which were granted accreditation seek to achieve the academic outcomes of the programs that emanate from the international accreditation standards of ABET by a periodic continuous comprehensive evaluation system of all activities of the teaching process. Internal accreditation committees are formed in the engineering departments consisting of academic staff, administrative professionals and specialists with experience in monitoring and evaluation. The Faculty of Engineering has benefited from achieving the minimum standards of accreditation in improving the quality of learning outcomes and obtaining accredited university degrees similar to any degree in an accredited American university. The engineering departments also seek to improve the infrastructure and provision of equipment appropriate to the standards through obtaining institutional support. Despite the existence of some obstacles and challenges facing the engineering departments, they have benefited from accreditation. It was recommended to apply accreditation standards for all academic majors in universities for their importance for students, faculty members and the profession.